House 360 - Ísak Nói Guðnason 2002- (2024)
I still remember going to my grandmother’s house during summers with my parents. The trees surround the property creating a pocket of grass with no wind but still bright and sunny. The absence of wind is rare in Iceland. There were many family occasions there, my grandma even had her wedding with the love of her life there. I realize that not everyone is so lucky to have access to a space such as her garden and so my project aims to create such a space for the future generations of Sandgerði by providing removable modular homes for current ones.